Identification and functional analysis of LecRLK genes in Taxodium ‘Zhongshanshan’ - Jinbo Guo; Hao Duan; Lei Xuan; Ziyang Wang; Jianfeng Hua; Chaoguang Yu; Yunlong Yin; Mingzhi Li; Ying Yang (PeerJ, 2019)
Background Lectin receptor-like protein kinases (LecRLKs) can transform external stimuli into intracellular signals and play important regulatory roles in plant development and response to environmental stressors. However, research on the LecRLK gene family of conifers has seldom been reported. Methods Putative LecRLK genes were identified in the transcriptome of Taxodium ‘Zhongshanshan’. The classification, domain structures, subcellular localization prediction, and expression patterns of LecRLK genes, as well as co-expressed genes, were analyzed using bioinformatics methods. Fifteen representative genes were further selected for qRT-PCR analysis in six tissues and under five different environmental stressor conditions. Results In total, 297 LecRLK genes were identified, including 155 G-type, 140 L-type, and 2 C-type. According to the classification, G-type and L-type LecRLK genes both can be organized into seven groups. The domain architecture of G-type proteins were more complex compared with that of L- and C-type proteins. Conservative motifs were found in G-type and L-type diverse lectin domains. Prediction and transient expression experiments to determine subcellular localization showed that LecRLKs were mainly concentrated in the cell membrane system, and some members were located at multiple sites at the same time. RNA-seq-based transcriptomics analysis suggested functional redundancy and divergence within each group. Unigenes co-expressed with LecRLKs in the transcriptome were found to be enriched in pathways related to signal transduction and environmental adaptation. Furthermore, qRT-PCR analysis of representative genes showed evidence of functional divergence between different groups. Conclusions This is the first study to conduct an identification and expression analysis of the LecRLK gene family in Taxodium. These results provide a basis for future studies on the evolution and function of this important gene family in Taxodium.